Effects of the degree of crosslinking and test rate on the tensile properties of a crosslinked polyacrylic pressure‐sensitive adhesive and vulcanized rubber. Issue 13 (11th November 2018) - Kashihara, Yusuke; Okada, Shun; Urahama, Yoshiaki; Hikasa, Shigeki; Makuta, Satoshi; Fujiwara, Kazuko; Fujii, Syuji; Nakamura, Yoshinobu
ABSTRACT: The effects of the tensile test rate on the properties of a pressure‐sensitive adhesive (PSA) and of vulcanized rubber were ascertained and compared, using a poly( n ‐butyl acrylate‐acrylic acid) random copolymer with varying degrees of crosslinking as the PSA. The 100% modulus of the PSA was found to increase along with the crosslinking degree and with faster tensile test rates. In contrast, the 100% modulus of the vulcanized rubber did not exhibit any test rate dependence. To assess this effect, the molecular weights between chemical and physical crosslinking points were determined via equilibrium swelling, dynamic mechanical analysis, and tensile tests. The proportion of physical crosslinking points was found to be far larger in the crosslinked PSA. Because these entanglement points can readily disentangle in response to slow deformation, variations in the test rate only affected the PSA. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47272. Abstract :